Modeling institutions, start-ups and productivity during transition - Zuzana Brixiova; Balázs Égert (Center for Economic Studies and ifo Institute (CESifo), 2010)
The transition paths from plan to market have varied markedly across countries. Central and Eastern European and the Baltic countries, which opted for a fast and profound transformation of their institutions including business climates, rapidly narrowed the productivity gap with advanced economies. In contrast, in countries of the Commonwealth of Independent States, which embarked on reforms later and contented with less depth, the productivity gap remains substantial. While the literature has focused mainly on empirical studies, this paper develops a dynamic search model of the firm start-ups that is consistent with the above trends. The model shows that an enabling institutional set up stimulates start-ups of highly productive firms at an earlier stage of transition, underscoring the importance of reforms. The role of the state sector as an employer during transition rises in countries where reforming institutions is particularly costly.
Keywords: O43; O14; O57; C61; C63; 330; start-ups; dynamic search model; business climate; productivity; transition; Übergangswirtschaft; Unternehmensgründung; Suchtheorie; Institutionelle Infrastruktur; Produktivität; Theorie; Osteuropa